EKSPLORASI DAN UJI BIOLARVASIDA FRAKSI DAUN TANAMAN MARGA Annona TERHADAP LARVA NYAMUK Aedes aegypti DAN Culex quinquefasciatus - Hamidah Hamidah (The East Java Biological Society, 2001)
The research aim wants to know: (1) Lethal Concentration (LC90) leaves fraction of Annona muricata, Annona squamosal, and Annona reticulate that caused death of third instar larvae of Aedes aegypti and Culex quinguefasciatus. The experimental method was used in research with completely random design. Each concentration was replicated five times. After introducing bioassay was done, five concentration used at real bioassay. For knowing LC90 from leaves fraction of Annona muricata, Annona squamosa and Annona reticulata, the data was analyzed by probit analysis. The result from this research showed that LC90 of leaves fraction methanol of leaves fration methanol was the highest of Annona squamosa (404 ppm) and the lower LC90 was leaves fraction n.heksa Annona reticulata (1894 ppm).